Legal design: A catalyst for Environmental Social and Governance (ESG) and sustainable business practices - Ebru Metin (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2024)
This paper examines how the application of Stakeholder Theory and legal design can enhance corporate compliance with regulatory requirements, particularly within Environmental, Social, and Governance (ESG) frameworks. By utilizing visual aids, design patterns, plain language, and human-centered design principles, legal design transforms complex legal information into accessible and actionable information, fostering better understanding and decision-making among stakeholders. This approach not only improves regulatory compliance but also aligns with ethical standards and social responsibilities, which enhances stakeholder trust and engagement. Furthermore, the integration of legal design into corporate compliance strategies supports long-term sustainability and digital transformation, contributing to the creation of value for all stakeholders.
Keywords: K32; M14; D21; Q01; L21; O32; 330; Legal Design; ESG; Regulatory Compliance; Digital Transformation; Stakeholder Theory; Sustainability